2017
DOI: 10.1021/acs.molpharmaceut.7b00578
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Deep Learning With Multiple Machine Learning Methods and Metrics Using Diverse Drug Discovery Data Sets

Abstract: Machine learning methods have been applied to many datasets in pharmaceutical research for several decades. The relative ease and availability of fingerprint type molecular descriptors paired with Bayesian methods resulted in the widespread use of this approach for a diverse array of endpoints relevant to drug discovery. Deep learning is the latest machine learning algorithm attracting attention for many of pharmaceutical applications from docking to virtual screening. Deep learning is based on an artificial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
252
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(266 citation statements)
references
References 124 publications
2
252
0
Order By: Relevance
“…Although there are several chemistry problems where DNNs outperform other shallow machine learning methods 49,59,60 , here the MFP+RF performed best with the small dataset of 676 molecules in the 5-and 12-class predictions. However, in the 3class task with the small dataset, and all the tasks with the large dataset, the two models produced accuracies that were nearly indistinguishable.…”
Section: Discussionmentioning
confidence: 85%
“…Although there are several chemistry problems where DNNs outperform other shallow machine learning methods 49,59,60 , here the MFP+RF performed best with the small dataset of 676 molecules in the 5-and 12-class predictions. However, in the 3class task with the small dataset, and all the tasks with the large dataset, the two models produced accuracies that were nearly indistinguishable.…”
Section: Discussionmentioning
confidence: 85%
“…[71] who showed that positive transfer learning is conditioned by sharing a significant amount of input data whose labels are correlated. In general, other studies [72,73,74,75] reported that FNN performs the best for a variety of chemoinformatics problem, but only for some metrics and datasets.…”
Section: Deep Learning For Chemoinformaticsmentioning
confidence: 92%
“…Deep neural networks model is similar to neural networks in the brain. It stimulates the process of signal conduction between neurons (Junshui, Sheridan, Andy, Dahl, & Vladimir, 2015;Korotcov, Tkachenko, Russo, & Ekins, 2017;Lecun, Bengio, & Hinton, 2015;Ramsundar et al, 2017). Three types of layers constitute the whole network, as shown in Figure S1.…”
Section: Deep Neural Networkmentioning
confidence: 99%
“…Recall reflects the ability of a model to find all the right cases within a data set and precision expresses the proportion of the data points are correctly predicted as actives. F1 score is the harmonic mean of precision and recall (Cai et al, 2018;Korotcov et al, 2017;Podlewska, Czarnecki, Kafel, & Bojarski, 2017). In general, accuracy is used to evaluate the performance of the classification model.…”
Section: Performance Evaluationmentioning
confidence: 99%